JUMLAH PENDUDUK SEBAGAI PEMODERASI PENGARUH KEMANDIRIAN KEUANGAN DAN LEVEL OF CAPITAL OUTLAY TERHADAP FINANCIAL DISTRESS - Mahayani, Dwi Indri Mutia; Gayatri, . (E-Jurnal Akuntansi, 2017)
Financial distress in public sector caused by internal or external factor and described by the government’s incapable in giving the standard public service. The purpose of this study is to determine the effect of fiscal autonomy and level of capital outlay (LCO) on financial distress using citizen population as moderating variabel This study covers 9 districts/cities in Bali Province and using data from budget realization report obtained at the Bali Provincial Finance Bureau and amount of citizen population obtained at the Central Bureau of Statistics of Bali in 2010-2015, so the sample is consist of 54 data. This research using linier regression analysis and moderated regression analysis (MRA).The test results showed fiscal autonomy and LCO have positive and significant impact on financial distress. The moderation’s results showed citizen population strengthen the effect of fiscal autonomy on financial distress and citizen population weaken the effect of fiscal autonomy on financial distress.
Keywords: autonomy, LCO, financial distress, citizen